Bibliometric mapping of non-invasive brain stimulation techniques (NIBS) for fluent speech production - Medeiros, Wesley; Barros, Tayná; Caixeta, Fabio V. (Frontiers in Human Neuroscience, 2023)
Speech production is a finely regulated process, with many aspects that still elude comprehension. From a motor perspective, speech involves the coordination of over a hundred different muscles. As science and technology evolve, new approaches are used to study speech production and treat its disorders, and there is growing interest in the use of non-invasive modulation by means of transcranial magnetic stimulation (TMS) and transcranial direct current stimulation (tDCS). Here we analyzed data obtained from Scopus (Elsevier) using VosViewer to provide an overview of bibliographic mapping of citation, co-occurrence of keywords, co-citation and bibliographic coupling of NIBS use in speech fluency research. In total, 347 documents met our search criteria, and we found that 55% of these came from only three countries (USA, Germany and Italy), with emerging economies such as Brazil and China becoming relevant in this topic recently. Most documents were published in this last decade, with 2022 being the most productive yet, showing brain stimulation has untapped potential for the field. Keyword analysis indicates a move away from basic research of brain lateralization and reaction time, towards the current focus on randomized controlled clinical trials and experimental blinding. Finally, we discuss how NIBS have gained prominence as tools in speech therapy and research, and highlight potential paths to be explored for new researchers in the area.